2001
DOI: 10.1038/sj.onc.1204230
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis using DNA microarrays demonstrates that E2F-1 up-regulates expression of DNA replication genes including replication protein A2

Abstract: The transcription factor E2F-1 plays a pivotal role in the regulation of G1/S transition in higher eukaryotes cell cycle. We used a cell line containing an inducible E2F-1 and oligonucleotide microarray analysis to identify novel E2F target genes. We show that E2F-1 up-regulates the expression of a number of genes coding for components of the DNA replication machinery. Among them is the gene coding for the 32 Kd subunit of replication protein A (RPA2). Replication protein A is the most abundant single strand D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 51 publications
2
51
1
Order By: Relevance
“…In synchronised murine cells, TS mRNA and TS activity increased as cells reach S-phase (Navalgund et al, 1980;Nagarajan and Johnson, 1989). Ectopic over-expression of E2F transcription factors leads to upregulation of TS transcripts (Ishida et al, 2001;Kalma et al, 2001;Polager et al, 2002). Since E2F transcription factors are one of the main effectors of the G 1 /S transition (Fan and Bertino, 1997) that control the expression of a number of genes required for DNA synthesis (DeGregori et al, 1995), these studies reinforced the hypothesis that TS is a S-phasedependent enzyme.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In synchronised murine cells, TS mRNA and TS activity increased as cells reach S-phase (Navalgund et al, 1980;Nagarajan and Johnson, 1989). Ectopic over-expression of E2F transcription factors leads to upregulation of TS transcripts (Ishida et al, 2001;Kalma et al, 2001;Polager et al, 2002). Since E2F transcription factors are one of the main effectors of the G 1 /S transition (Fan and Bertino, 1997) that control the expression of a number of genes required for DNA synthesis (DeGregori et al, 1995), these studies reinforced the hypothesis that TS is a S-phasedependent enzyme.…”
Section: Discussionmentioning
confidence: 83%
“…In rodent cells, microarray analysis has shown that ectopic expression of various E2F family members increase TS mRNA levels (Ishida et al, 2001;Kalma et al, 2001;Polager et al, 2002). In human cells, two E2F consensus binding sites are found in the inverted repeat of the TS promoter.…”
mentioning
confidence: 99%
“…Semiquantitative RT-PCR was performed essentially as described. 49 Primers specific for GAPDH, 5 0 -ACCACAGTCCATGCCAT CAC and 5 0 -TCCACCACCCTGTTGCTGTA, ASPP1, 5 0 -GAAATGA ACGTCCCATACCC and 5 0 -TTTCAGCAGACAGATTGCC, ASPP2, E2F activates proapoptotic cofactors of p53 T Hershko et al 5 0 -AAATCTTCCCCAGCAAGCC and 5 0 -GCACTTTCTTCTCTTTCTCCC, JMY, 5 0 -ATAAATCCACTCCCATCCCC and 5 0 -CCCCTTTCCTTATTTGT GCC, TP53INP1, 5 0 -AAACCTTCTCATTGAACATCCC and 5 0 -CCATTGT GCTTGACTTGCC, were used in PCR amplifications. Western blot analysis was performed essentially as described.…”
Section: Rt-pcr and Western Blottingmentioning
confidence: 99%
“…More recently identified E2F targets include genes whose products function in DNA repair (e.g., Msh2, Mlh1, Rad51), cell cycle checkpoints (e.g., Chk1) and mitotic regulation (e.g., Cdc2, cyclin B, Cdc35a, Bub3, Smc2) (Ishida et al, 2001;Kalma et al, 2001;Ma et al, 2002;Weinmann et al, 2002;Wells et al, 2002;reviewed in Stevaux and Dyson, 2002;Cam and Dynlacht, 2003).…”
Section: Introductionmentioning
confidence: 99%